Taxonomic revision of the troglophile Spariolenus spiders (Araneae: Sparassidae) in South and West Asia - Moradmand, Majid; Wesal, Mohammad Wasil; Kulkarni, Siddharth (Zootaxa, 2023)
The taxonomy of the genus Spariolenus Simon, 1880 (Heteropodinae) is updated in its entire distribution range in South and West Asia. Newly collected specimens and historical museum material were studied, some date back to more than 124 years. Four new species are described as Spariolenus omidvarbrothers sp. n. (male, female) from southeastern Iran, S. baluchistanicus sp. n. (female) from Pakistan and, S. bakasura sp. n. (male, female) and S. kabandha sp. n. (female) from the Western Ghats and northern regions of India, respectively; specimens of the latter three species had been previously incorrectly identified as S. tigris Simon, 1880. Spariolenus lindbergi (Roewer, 1962) comb. nov. is transferred from the genus Heteropoda Latreille, 1804. We discovered and described its male for the first time, along with redescription of the female using recently collected material near the type locality from Afghanistan. Two species, Spariolenus mansourii Moradmand, 2017 (Iran) and S. secundus Jäger, 2006 (Oman) are recorded from new geographic localities. A distribution map of all extant Spariolenus species with updated records is presented.